Sustainability, innovation and procurement - Mangla, Sachin K.; Luthra, Sunil (Boca Raton, FL : CRC Press/Taylor & Francis, 2020)
"Sustainable procurement is the pursuit of sustainable development objectives through the purchasing and supply process, while balancing environmental, social, and economic objectives. This book will help readers develop new contemporary knowledge about frameworks, innovative tools and techniques to achieve sustainability in public as well as private procurement practices. The book will enable scholars and practitioners working in the domain of sustainable procurement to improve the overall performance of the supply chain and further achieve UN SDGs, by making various decisions at the planning and strategic phase of the business"--
Business model innovation in sustainable procurement : A case study on organic farming in India / Tuhin Sengupta, Indian Institute of Management Indore, Suwarna Shukla, Indian Institute of Management Indore -- Additive manufacturing : Sustainability, innovation and procurement / Saty Dev, Department of Mechanical Engineering, Motilal Nehru, National Institute of Technology Allahabad, India, Rajeev Srivastava, Department of Mechanical Engineering, Motilal Nehru National Institute of Technology, Allahabad, India, Pushpendra Yadav, Department of Mechanical Engineering, Faculty of Engineering, Dayalbagh Educational Institute Agra, India, Surya Prakash, Department of Mechanical Engineering, BML Munjal University, Gurugram, India -- Evaluation of motivational factors for sustainable supplier collaboration in Indian industries / Vernika Agarwal & K. Mathiyazhagan, Amity International Business School, Amity University, Sector 125, Noida, India, Department of Mechanical Engineering, Amity School of Engineering & Technology, Amity University, Sector 125, Noida, India.
OCLC-licensed vendor bibliographic record.
Keywords: Industrial procurement; Sustainable development; BUSINESS & ECONOMICS / Purchasing & Buying; TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Industrial Design / General